Academic Procrastination: Its Effect on the Learning Productivity of Senior High School Students in Mindanao State University-Sulu - Alih, Nur-In I.; Alvarez, Almarezza L. (Indonesian Community Empowerment Journal, 2021)
Procrastination has become common practice for many students, which has affected their learning productivity. This study aimed to determine the effect of procrastination on learning productivity. This research was an observational study with a descriptive design. The setting of the study was Mindanao State University Sulu- Senior High School department campus which only focused on STEM 12 Strand, which is located at Capitol Site, Jolo, Sulu. The respondents of this study were the Grade 12 STEM strand senior high students from all sections in Mindanao State University-Sulu. This study used the Likert scale to measure the respondents’ agreement level with various statements about some opinions and attitudes. The researchers chose the close-ended type of questionnaire as the research instrument of the study. The results stated that most of the respondents agreed that the effect of procrastination on the students’ learning productivity made them feel like they were pressured with the tasks they could not think about properly, which got the highest obtained mean of 3.88. In conclusion, parental motivation, guidance, and advice would greatly help motivate and boost the students to do their work in light of modular learning. Teachers, alongside student leaders, must initiate a seminar addressing time management to overcome procrastination among students.